AGENTES BIOLÓGICOS, EXTRATOS VEGETAIS E PRODUTOS QUÍMICOS NO CONTROLE DE FUNGOS ASSOCIADOS A DOENÇAS DE TRONCO DA VIDEIRA - Rusin, Carine (2017)
The fungal diseases that affect grapevine are a very limiting factor for viticulture and difficult to control. In this context, this research aims to verify the effect of biological agents and plant extracts on the control of Botryosphaeriaceae fungi, agents of vines’ death and decline. On the in vitro experiments, were used three isolated samples of Lasiodiplodia theobromae, two of Lasiodiplodia brasiliense and one of Botryosphaeria sp. On the first in vitro experiment were tested the efficiency of five doses of clove, cinnamon, garlic, rosemary and lemon grass extracts to control the mycelial growth of isolated samples of fungi. On the second one, the following treatments were: difeconazole, tebuconazole, mancozeb, sulfur, pyraclostrobin, fosetyl-Al, azoxystrobin, chitosan, Trichoderma harzianum and Bacillus subtilis. In vivo experiments of pruning wounds’ protection were performed in a greenhouse with seedling vines of Bordô and Syrah, evaluating the efficiency of six treatments: fosetil-Al, tebuconazole, Trichoderma harzianum, Bacillus subtilis, garlic extract and clove extract. After 24 hours of treatments application the vines were inoculated with Botryosphaeria sp. or Lasiodiplodia theobromae fungi. The experiments were performed during two vegetative cycles: 2015/2016 and 2016/2017. Were avaliated the inner vascular decoloration area, the percentual of Botryosphaeriaceae fungus reisolation, fresh mass of pruning material, peroxidase activity, fluorescence, chlorophyll index, phenological stages, branches length and leaf area of the plants. Clove and garlic extracts, tebuconazole, pyraclostrobin, mancozeb, fosetyl-Al products and B. subtillis reduced mycelial growth of the pathogens by direct contact by more than 90%. In vivo, the use of T. harzianum decreased the reisolation rates of Botryosphaeriaceae fungi on the four experiments. From the results found, it was concluded that garlic and clove extracts, tebuconazole, mancozeb, fosetyl-Al and pyraclostrobin, chemical products, and T. harzianum and B. subtillis, agents of biological control, have efficiency in in vitro control of the tested pathogens. The use of T. harzianum proved to be an effective option in the protection of wounds of both cultivars, do not modifying the plant physiological conditions.